2020
DOI: 10.1186/s13058-020-01271-0
|View full text |Cite
|
Sign up to set email alerts
|

Everolimus versus alpelisib in advanced hormone receptor-positive HER2-negative breast cancer: targeting different nodes of the PI3K/AKT/mTORC1 pathway with different clinical implications

Abstract: Background: The PI3K/AKT/mTORC1 axis is implicated in hormone receptor-positive HER2-negative metastatic breast cancer (HR+ HER2− mBC) resistance to anti-estrogen treatments. Based on results of the BOLERO-2 trial, the mTORC1 inhibitor everolimus in combination with the steroidal aromatase inhibitor (AI) exemestane has become a standard treatment for patients with HR+ HER2− mBC resistant to prior non-steroidal AI therapy. In the recent SOLAR-1 trial, the inhibitor of the PI3K alpha subunit (p110α) alpelisib in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 58 publications
0
17
0
2
Order By: Relevance
“…In addition, in May 2019, alpelisib in combination with fulvestrant was approved for PIK3CA mutated hormone-positive metastatic breast cancer based on the SOLAR-1 trial which reported PFS of 11 months [ 22 ]. Everolimus inhibits mTORC1 downstream of PI3K and may remain a valuable treatment option for patients who do not qualify for or who progress on alpelisib [ 23 ]. As new treatment combinations become available, more clinical trials will be needed to assess the optimal sequence of therapies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in May 2019, alpelisib in combination with fulvestrant was approved for PIK3CA mutated hormone-positive metastatic breast cancer based on the SOLAR-1 trial which reported PFS of 11 months [ 22 ]. Everolimus inhibits mTORC1 downstream of PI3K and may remain a valuable treatment option for patients who do not qualify for or who progress on alpelisib [ 23 ]. As new treatment combinations become available, more clinical trials will be needed to assess the optimal sequence of therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Although the widespread use of alpelisib in the daily treatment of HR+/HER2-aBC patients bearing PIK3CA-mutated tumors might be limited by several factors, including the lack of an extensive tumor genomic profiling in several cancer centers, the suboptimal safety profile of alpelisib and recent labels limiting alpelisib use in Europe and Italy to patients previously treated with single-agent endocrine therapy (which has now been replaced by endocrine therapy plus CDK 4/6 inhibitor-based combinations as a standard-of-care first-line therapy), the alpelisib-fulvestrant combination remains a potentially useful therapy that could be used in up to 40% of all HR+/HER2-aBC patients. Therefore, since the incidence of severe (grade 3 or 4) hyperglycemia is common with alpelisib (actually more common than with EVE) despite the precocious use of metformin in the SOLAR-1 study (24), exploring strategies to prevent or promptly manage alpelisib-induced hyperglycemia/diabetes is a clinically relevant issue, especially for patients with normal baseline blood glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the crucial role of the PI3K/AKT/mTOR pathway in stimulating tumor cell proliferation, changing metabolism, and inhibiting apoptosis is widely accepted in breast cancer [ 50 ]. Some potential interactions between estrogen receptors and the PI3K/AKT/mTOR pathway have been documented [ 51 ].…”
Section: Discussionmentioning
confidence: 99%